Asbestosis: assessment by bronchoalveolar lavage and measurement of pulmonary epithelial permeability. Issue 7 (July 1985) - Gellert, A R; Langford, J A; Winter, R J; Uthayakumar, S; Sinha, G; Rudd, R M
Abstract : Thirty two patients with asbestosis were assessed by means of bronchoalveolar lavage (27 patients) and the half time clearance from lungs to blood (T1/2LB) of an inhaled aerosol of diethylenetriamine pentacetate (DTPA) labelled with technetium 99m (32 patients). T1/2LB was also measured in 20 non-smoking normal individuals and 17 smokers without a history of exposure to asbestos. Thirteen patients (46%) showed an increase in the percentage of neutrophils with or without an increase in the percentage of eosinophils and eight (29%) showed an increased percentage of lymphocytes. The number of neutrophils plus eosinophils expressed as a percentage of the total count was positively correlated with the length of the history of disease (r = 0.53, p less than 0.025) and greater percentages were associated with more severe impairment of lung function. Smokers had lower percentages of lymphocytes than non-smokers (p less than 0.002) and showed increased proportions of neutrophils and eosinophils more often than non-smokers (p less than 0.05). In 18 non-smokers with asbestosis the mean T1/2LB was 33.8 (range 10.0-62.0) minutes, significantly less than 57.2 (30.5-109) minutes in 20 non-smoking normal subjects (p less than 0.002). In non-smokers shorter T1/2LB correlated with a longer time since first exposure to asbestos (r = -0.65, p less than 0.005), longer duration of exposure (r = -0.70, p less than 0.001), and a shorter time since last exposure (r = 0.59, p less than 0.01). Shorter T1/2LB was also associated with increased inflammatory activity as shown by higher bronchoalveolar lavage cell counts (r = -0.53, p less than 0.025) and higher combined percentages of neutrophils, eosinophils, and lymphocytes (r = -0.47, p less than 0.05). The techniques of bronchoalveolar lavage and measurement of inhaled solute clearance may be useful in assessing inflammatory activity in asbestosis.